MHC class II expression in lung cancer. (October 2017) - He, Yayi; Rozeboom, Leslie; Rivard, Christopher J; Ellison, Kim; Dziadziuszko, Rafal; Yu, Hui; Zhou, Caicun; Hirsch, Fred R
Highlights: MHC Class II was expressed both in NSCLC cell lines and tissues. MHC Class II was not detected in SCLC cell lines or tissue tumor cells. Lower expression of MHC Class II on SCLC may be a means of escaping anti-cancer immunity. Higher MHC Class II expression on TILs was correlated with better prognosis in NSCLC. Abstract: Background: Immunotherapy is an exciting development in lung cancer research. In this study we described major histocompatibility complex (MHC) Class II protein expression in lung cancer cell lines and patient tissues. Methods: We studied MHC Class II (DP, DQ, DR) (CR3/43, Abcam) protein expression in 55 non-small cell lung cancer (NSCLC) cell lines, 42 small cell lung cancer (SCLC) cell lines and 278 lung cancer patient tissues by immunohistochemistry (IHC). Results: Seven (12.7%) NSCLC cell lines were positive for MHC Class II. No SCLC cell lines were found to be MHC Class II positive. We assessed 139 lung cancer samples available in the Hirsch Lab for MHC Class II. There was no positive MHC Class II staining on SCLC tumor cells. MHC Class II expression on TILs in SCLC was significantly lower than that on TILs in NSCLC (P ＜ 0.001). MHC Class II was also assessed in an additional 139 NSCLC tumor tissues from Medical University of Gdansk, Poland. Patients with positive staining of MHC Class II on TILs had longer regression-free survival (RFS) and overall survival (OS) than those whose TILs were MHC Class II negative (2.980 years, 95% CI 1.628–4.332 vs. 1.050 years, 95% CI 0.556–1.554, P = 0.028) (3.230 years, 95% CI 2.617–3.843 vs. 1.390 years, 95% CI 0.629–2.151, P = 0.014). Conclusions: MHC Class II was expressed both in NSCLC cell lines and tissues. However, MHC Class II was not detected in SCLC cell lines or tissue tumor cells. MHC Class II expression was lower on SCLC TILs than on NSCLC TILs. Loss of expression of MHC Class II on SCLC tumor cells and reduced expression on SCLC TILs may be a means of escaping anti-cancer immunity. Higher MHC Class II expression on TILs was correlated with better prognosis in patients with NSCLC.